New insights into the molecular phylogeny and taxonomy of mormyrids (Osteoglossiformes, Actinopterygii) in northern East Africa. (26th September 2017) - Levin, Boris A.; Golubtsov, Alexander S.
Abstract: Based on morphological data and analysis of mitochondrial cytochrome b gene and nuclear ( S7 intron 1 ) DNA sequences, the phylogenetic relationships of all Pollimyrus species known from the Omo‐Turkana enclosed basin and Nile system below the Murchison Falls were solved. A mormyrid " Pollimyrus " petherici is distantly related to all other studied Pollimyrus species and clusters together with Cyphomyrus species forming with the later a monophyletic group. Moreover, the West African (but not the Congo River) populations of Cyphomyrus psittacus, the type species of the genus, seem to be conspecific to C. petherici . That is, the range of the genus Cyphomyrus is extended toward the Nile and Omo‐Turkana basins. This genus belongs to the large clade widely distributed in sub‐Saharian Africa and characterized by the presence of a chin appendage. Significance of this character for mormyrid phylogeny is discussed. Two distinct lineages of Pollimyrus occurring sympatrically in the White Nile tributaries and previously reported as the light and dark forms of Pollimyrus isidori together with five other congeneric species studied form a monophyletic group. The light form apparently represents P. isidori distributed in the Nile system downstream of the Murchison Falls and West Africa; the dark‐colored form (designated as Pollimyrus "D") represents a distinct phylogenetic lineage inhabiting both the Omo‐Turkana and the White Nile basin. Morphological and ecological data suggest that this form may be conspecific to East African Pollimyrus nigricans or most probably represents a new species. Abstract : We clarified molecular phylogeny and taxonomy of Pollimyrus species from the Omo‐Turkana basin and Nile system below the Murchison Falls. ' Pollimyrus ' petherici is distantly related to the genus Pollimyrus and clusters together with Cyphomyrus species. The range of the genus Cyphomyrus is extended towards the Nile and Omo‐Turkana basins. Two distinct lineages of Pollimyrus isidori occurring sympatrically in the White Nile tributaries and previously reported as the light and dark forms form a monophyletic group together with other congeneric species.